Výskyt oocyst Toxoplasma gondii v trusu kocek - Svobodová, V; Svoboda, M (Veterinarni medicina, 1986)
Within two years and a half, the faeces of 620 cats coming from Brno and the area around the city were subjected to parasitological examination with special regard to the occurrence of the oocysts of Toxoplasma gondii. Sucrose solution at the specific weight of 1,150 was used as flotation medium. Oocysts of Toxoplasma gondii were eliminated by eight cats (1.29%) at the age from 16 days to 1.5 years. Six of the eight cats were younger than seven months. The Toxoplasma gondii oocysts were eliminated by the cats for 1-16 days while exhibiting signs of short-term scours and swelling of lymph nodes. In all cases the oocysts of Toxoplasma gondii were produced in the summer and autumn seasons (June-December). During the patent period, other coccidia (Isospora felis and Isospora rivolta) were also present in the cats.
Keywords: Feces; Cats; zvířata; feces; Toxoplasma; počet parazitárních vajíček; Parasite Egg Count; kočky; Animals